(untitled) (Research, Society and Development, 2021)
Objective: To identify the prevalence of hemoglobinopathies in pregnant women screened at the Dona Evangelina Rosa Maternity Hospital in Teresina, state of Piauí. Methods: We analyzed 19 pregnant women with altered hemoglobin levels, screened at Dona Evangelina Rosa Maternity, during the period from October 2015 to june 2016. The data was organized into a database in Microsoft Office Excel. And the analysis performed using the Statistical Package for the Social Sciences® (SPSS) program version 23.0. Results: Sickle cell trait (Hb AS and AC) had a prevalence of 5.17% (1:19). Of the 19 pregnant women with altered hemoglobin levels, the most prevalent was Hb AS with (78.94%), followed by Hb AC totaling (21.05%). Most of the pregnant women who had hemoglobinopathies were brown ethnicity (69.15%), followed by white (5.25%). Most of the pregnant women with alterations were predominantly from cities in the state of Piauí, especially Teresina (52.63%) followed by José de Freitas (15.78%). Prevalence was also observed in the age group of 31 to 35 years (42.10%), schooling with incomplete mean (57.89%), gestational age in the third trimester (94.73%), gestational history of 2 to 3 pregnancies (47.36%), type of delivery with cesarean section (52.63%), absence of abortion history (78.94%) in pregnant women with hemoglobinopathies. Conclusion: The prevalence of abnormal hemoglobins in triaged pregnant women identified sickle cell traits (Hb AS and AC) evidencing the need for interventions, such as actions focused on the care and care of the pregnant woman and the child during the first year of life, as well as genetic counseling for the future pregnancy.